Noninflammatory necrotizing vasculopathy in lupus nephritis: a single-center experience. (January 2014) - Chu, H; Wu, LH; Song, D; Yu, F; Zhao, MH
In this study, we assessed the clinicopathological features of lupus nephritis patients with renal noninflammatory necrotizing vasculopathy (NNV). A total of 142 renal biopsies with lupus nephritis were reviewed, including nine cases presented with NNV and 36 without renal vascular lesions. The comparisons of clinical, laboratory and pathological features, treatments, as well as renal outcome between the two groups were further performed. In comparison with the no renal vascular lesions group, patients with NNV changes had significantly higher proportions of noninfection leukocyturia ( p  = 0.013) and leukocytopenia ( p  = 0.042), significantly higher serum creatinine ( p  = 0.012), lower hemoglobin ( p  = 0.002) and serum C3 ( p  < 0.001) levels. Renal pathological activity indices and chronicity indices were significantly higher in the NNV group ( p =  0.002 and p  = 0.006, respectively) than those in the no vascular lesions group. Regarding renal prognosis, the presence of NNV was not a risk factor for renal outcome ( p  = 0.327). In conclusion, NNV was not infrequent in renal biopsies of lupus nephritis. It was commonly associated with active clinical status and proliferative glomerular lesions of lupus.